Improving Mathematical Reasoning Ability by Developing Mathematical Learning Tools Based on Guided Discovery Models - Randika Irwa Risky; Hendra Syarifuddin; I Made Arnawa; Suherman (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2022)
Junior high school students low mathematical reasoning ability is one reason for carrying out this research. This study aims to produce a valid, practical, and effective Guided Discovery-based Mathematics Learning Tool to facilitate students' mathematical reasoning abilities. This study is development research carried out with the Plomp development model. This model has three stages: preliminary investigation, prototyping stage, and assessment phase. This research was conducted at SMP Negeri 4 Padang. The instruments used to collect data are questionnaires, documentation, test questions, and interviews—data analysis using quantitative and qualitative data analysis techniques. The results showed that the Guided Discovery-based Mathematics Learning Toolkit developed was categorized as valid (3.30 for RPP and 3.35 for LKPD) and very practical, respectively, 82.6% and 85% (for RPP and LKPD). Meanwhile, based on the results of the test results of the mathematical reasoning ability test, it was found that 86.3% of students met the criteria for the success of the mathematical reasoning ability test > 80%, meaning that the guided discovery model-based learning device was very influential on mathematical reasoning abilities.